Pengaruh Media Promosi Perbankan Syariah Terhadap Minat Menabung Masyarakat di Bank Syariah Indonesia Kudus - Venomena Candrakuncaraningsih (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study is to explain how the promotion media for Sharia banks affects people's interest in saving at Indonesia Sharia Bank Kudus. This research focuses on promotion media through newspapers, television, and the internet. Quantitative description method is the method used in this study with linear regression as the analysis technique. The data is sourced from primary data through a questionnaire (questionnaire) distributed to the public. The results of the study explain that television and internet variables are still promotion media that still have a major influence on people's interest in saving at the Indonesia Sharia Bank Kudus. While the newspaper variable is a promotion media that has a lower influence, it shows that newspapers are no longer a powerful medium for promotion for the Indonesia Sharia Bank Kudus.